Pelatihan Teamwork Organisasi dengan Permainan Estafet Mengisi Air untuk Santriwati Pesantren Al Fatimiyah Lamongan - Sari, Pusvyta; Jannah, Ilmiyatul; Istiqomah, Cici Dzuriyyatul; Zahra, Aprilia; Insaniyah, Latifatul; Qolbiyah, Latifatul; Mufidah, Arsya Lu’lu’ul (Jaanur Elbarik Indonesia, 2025)
Organizations knowledge and teamwork strategy to achieve organizational success is important for the younger generation. Various methods can be used to convey this material, one of which is using games. The purpose of this training is delivering material on organizational success factors to haigh school students at the Islamic Boarding School, Al Fatimiyah Lamongan. Water estafet game develop to train softskill students with more interesting methode. The training was conducted using the ADDIE instructional development model, which includes the stages of Analyze, Design, Develop, Implementation, and Evaluation. The water estafet game was carried out in groups and aimed to complete two missions: answering questions and replacing cloudy water with clean water. Each group competed to complete the game and then jointly identified factors that influenced their success. Each participant reflected on the importance of these factors in achieving organizational success. The activity was attended cheerfully and enthusiastically.